Desarrollo de mercado clientes B2B Sushi Break (2023)
Abstract Purpose The main purpose of this project is to develop a new customer segment for Sushi Break Company. Currently, the Company uses a B2C model and wants to explore the B2B market. Design/methodology/approach The methodology is based on the business model CANVAS with the objective of increasing sales income in new market segments. Findings Sushi Break could offer a strong value proposition to B2B clients, leveraging its well-positioned brand. Practical implications To develop this new segment, Sushi Break must motivate its sales team and cultivate the new segment through new channels and customer relationships to optimize its operational capabilities. Originality/Value Currently, Sushi Break operates with a B2C model through its points of sale, serving end consumers. This project aims to increase sales revenue by offering catering services to B2B clients. Key Words Catering, Sushi Cali, Sushi, Sushi Catering, Business Catering, Business Sushi Catering, Gastronomic Experiences.